Atree, a remarkable new genus of the subfamily Brachistinae (Hymenoptera: Braconidae) and the first report of the tribe Diospilini from India - Ranjith, A.p.; van Achterberg, Cornelis; Priyadarsanan, Dharma Rajan (Zootaxa, 2022)
The braconid tribe Diospilini (subfamily Brachistinae) is reported for the first time from India with the description of a new genus, Atree, along with the description of a new species A. rajathae from south India. The newly described genus belongs to the Aspigonus genus group showing the presence of a wide, deep sculptured groove on the propleuron. Based on morphological affinities, two species reported from Taiwan which were earlier included in the genus Diospilus have been transferred to the new genus, as A. improcerus (Chou & Hsu, 1998) comb. nov. and A. validus (Chou & Hsu, 1998) comb. nov. A key to the Indomalayan and Palaearctic genera of Diospilini is provided along with the key to the species of Atree gen. nov.